2016
DOI: 10.1016/j.ijcac.2016.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Acute myocarditis mimicking myocardial infarction can misdirect the diagnostic approach

Abstract: a b s t r a c tAcute myocarditis is a well-recognized but rare manifestation of mostly viral infections. It can present with various clinical manifestations and may mimic myocardial infarction (MI) since patients usually present with chest pain, and the electrocardiographic changes similar to those observed in acute ST-elevation MI. We, herein, present such an extreme case of acute myocarditis characterized by dynamic ST segment elevation with reciprocal changes in the electrocardiogram.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…According to a case series study of 34 cases of myocarditis by Dec et al, only two cases had ST depression [ 1 ]. Focal STE with reciprocal changes as reported by Yildirim et al [ 4 ], STE in an adolescent male reported by Sharma et al [ 6 ], and STE in the inferior leads in a 15-year-old male as reported by Nisbet et al [ 9 ] highlight the pattern of EKG changes in this condition. Sharif et al compared two cases with a similar clinical presentation with STE, but one with normal coronary anatomy and myopericarditis on CMRI and the other with 90% LAD occlusion [ 10 ].…”
Section: Discussionmentioning
confidence: 65%
“…According to a case series study of 34 cases of myocarditis by Dec et al, only two cases had ST depression [ 1 ]. Focal STE with reciprocal changes as reported by Yildirim et al [ 4 ], STE in an adolescent male reported by Sharma et al [ 6 ], and STE in the inferior leads in a 15-year-old male as reported by Nisbet et al [ 9 ] highlight the pattern of EKG changes in this condition. Sharif et al compared two cases with a similar clinical presentation with STE, but one with normal coronary anatomy and myopericarditis on CMRI and the other with 90% LAD occlusion [ 10 ].…”
Section: Discussionmentioning
confidence: 65%
“…Despite compounding evidence establishing a possible causal relationship between COVID-19 infection and ACS, there are currently no sufficient data to categorically state that the advent of ACS observed among this subset of patients is due to an underlying medical condition or as a result of a direct cardiac effect of the virus itself. The overlapping laboratory evidence such as troponin I and clinical features of chest pain and dyspnea seen in both cases of myocarditis and myocardial infarction can also pose as a limiting factor in diagnosis [ 31 , 32 ].…”
Section: Reviewmentioning
confidence: 99%
“…A diffuse elevation of the ST segment and an upright divergence of the PR segment with ST-segment depression in lead aVR is common electrocardiogram (ECG) findings in patients with acute pericarditis [13]. Yildirim et al [14] reported different clinical pieces of evidence that the ECG signal of myocarditis was similar to that of Myocardial Infarction (MI). The reciprocal of the ST-segment elevation was observed in the ECG signal for acute myocarditis cases.…”
Section: Introductionmentioning
confidence: 99%
“…The reciprocal of the ST-segment elevation was observed in the ECG signal for acute myocarditis cases. It can have a variety of clinical symptoms and can be interpreted as myocardial infarction (MI) because patients typically have chest pain and electrocardiographic changes that are similar to those seen in acute ST-elevation MI [14]. Willemsen et al [15] analyzed three cases of chest pain.…”
Section: Introductionmentioning
confidence: 99%